Economic determinants of diet in older adults: systematic review. Issue 9 (12th June 2013) - Conklin, Annalijn I; Maguire, Eva R; Monsivais, Pablo
Abstract : Background and aims: Many economic factors are associated with diet, yet the evidence is generally cross-sectional. Older people are considered especially vulnerable to poor diets from negative changes to varied economic factors. This review extends current knowledge on known correlates to decipher actual economic determinants of diet in older adults. Methods: Eight bibliometric databases were searched between May and December 2012, supplemented by hand-searches, with no restrictions on publication date or country. Longitudinal studies, or reviews, were eligible when examining diet as a function of change in an economic factor in non-institutionalised adults ≥60 years. Data were extracted using a standardised evidence table and quality assessed before narrative synthesis. Results: We found nine original studies for inclusion, of which eight examined change from work to retirement and one evaluated a food price intervention. Designs were generally pre-post without controls and varying in follow-up. Studies reported mixed impact on food spending and/or food intake. Retirement was shown to both reduce and have no impact on food spending and to have either positive and negative, or positive and no impact on food intake. Subgroup differences were observed, especially between men and women. Conclusions: Despite ample research on economic correlates of older adults' diets, little is still known about actual economic determinants of diet in this population. Studies of retirement suggest divergent effects in some but not all older people. Robust high-quality longitudinal studies to decipher economic drivers of diet must be prioritised in research and policy as firm conclusions remain elusive.